Understanding our earth rocks and minerals - Coronet Instructional Media (Firm). (Chicago Coronet Instructional Media, 1977)
Describes the three classes of rocks, their formation, and uses.
Distributed by International Book Center.
Original copy in videocassette format.
Content consultant, Charles Shabica; classroom consultant, Ron Tyner.
Keywords: Rocks -- Juvenile films; Mineralogy -- Juvenile films; Geology